Microbiopsy a novel sampling technique to early detect dysplastic/malignant alterations in oral mucosal lesions: practicability by general dentists. (3rd February 2014) - Pentenero, Monica; Marino, Roberto; Tempia Valenta, Guido; Navone, Roberto; Gandolfo, Sergio
<x xml:space="preserve">Abstract</x> Background When used in oral medicine clinics, microbiopsy is able to obtain tissue fragments suitable for a highly sensitive first‐level diagnosis of dysplastic/malignant alterations in oral mucosal lesions. If feasible by general dentists, this sampling technique could reduce the diagnostic delay for oral malignant and premalignant lesions. This study assesses the adequacy of microbiopsy samples when taken by general dentists. Methods Fifty dentists, without specific training on oral medicine, volunteered for enrolment. They were given brief training and asked to prospectively sample any mucosal lesion observed during their routine practice. The sample adequacy features were assessed. Results The dentists sampled 152 lesions; there were 92.1% of adequate samples (140/152), and the BMZ was visible in 78.6% of these (110/140). Neither the clinical aspect nor lesion site affected either the adequacy or the presence of BMZ. Conclusions The high adequacy rate observed and the advantages histological specimens have over cytological ones go to support the feasibility of microbiopsy taken by general dentists for the characterization of oral mucosal lesions and in selecting those requiring further assessment in specialized oral medicine centres.